Hawai'i Is My Haven : Race and Indigeneity in the Black Pacific - Sharma, Nitasha Tamar, 1973- (Book collections on Project MUSE., 2021)
"Hawaiʻi Is My Haven is the first ethnography of Hawaiʻi's Black residents, providing a contemporary and on-the-ground documentation that expands historical and military histories of the Black Pacific. Drawing from a decade of fieldwork, it addresses two questions: What does the Pacific offer people of African descent? And what perspectives do Black people bring to help us better understand the Islands? Based on interviews with sixty civilian Black residents, including Hawaiʻi-born locals and transplants to the Islands, it engages debates in Black and Native Studies, Asian settler colonialism, and critical mixed race studies"--